Quechuismos en la Histórica Relación del Reino de Chile de Alonso de Ovalle - Gómez-Pablos, Beatriz (2019)
The present study analyzes the Quechua loanwords used in the work of Alonso de Ovalle, a 17th century jesuit chronicler of the Indies. Although the Histórica Relación has been studied from different points of view, to date no attention has been paid to the linguistic aspect. The present analysis examines the survival of these words in several lexicographic works published in the last eight years – the Argentinian Academy of Language (2008), Álvarez Vita (2009), Association of Academies of the Spanish Language(2010), the Chilean Academy of Language (2010), the Royal Spanish Academy of Language (2014), Miño-Garcés (2016), Calvo Pérez (2016) –, as well as the presence of other Americanisms.